Ephemeral rivers in the tropics - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Ephemeral rivers in the tropics: Hydrological processes and water resources assessment and management by Klas Sandström 1977 90pp ISBN91 7871 987 9